2015
DOI: 10.1063/1.4916784
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and structural effects on the high-temperature mechanical behavior of (1−x)(Na1/2Bi1/2)TiO3-xBaTiO3 ceramics

Abstract: Bismuth sodium titanate–barium titanate [(1−x)(Na1/2Bi1/2)TiO3-xBaTiO3, NBT-100xBT] is one of the most well studied lead-free piezoelectric materials due in large part to the high field-induced strain attainable in compositions near the morphotropic phase boundary (x = 0.06). The BaTiO3-rich side of the phase diagram, however, has not yet been as comprehensively studied, although it might be important for piezoelectric and positive temperature coefficient ceramic applications. In this work, we present a thorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 68 publications
5
7
0
Order By: Relevance
“…2. For higher temperatures the average structure appears to be cubic in agreement with previous reports [8,46].…”
Section: Resultssupporting
confidence: 91%
“…2. For higher temperatures the average structure appears to be cubic in agreement with previous reports [8,46].…”
Section: Resultssupporting
confidence: 91%
“…This might be ascribed to the combined effect of Bi 3+ (promoting tetragonality) and Yb 3+ (promoting pseudocubicity) substitution at A- and B-sites of BaTiO 3 , respectively. 2 , 11 In contrast, the dielectric anomaly associated with the tetragonal-to-orthorhombic phase transition shifts dramatically towards lower temperatures with increasing Bi/Yb content. Indeed, it drops from ∼12 °C for undoped BT to ∼ –18 °C for x = 0.005 and subsequently to ∼–37 °C for x = 0.01, eventually merging (at x = 0.02) with the orthorhombic-to-rhombohedral phase transition, which remained almost independent of the Bi/Yb content.…”
Section: Resultsmentioning
confidence: 98%
“…Pokorny et al 10 demonstrated that site occupancy in doped BaTiO 3 can be analysed by Raman spectroscopy, in particular the appearance of an A 1g mode was postulated to be a sufficient proof to ascertain either the presence of a dopant in the B-site or the existence of a Ti vacancy. In Bi-substituted BaTiO 3 , Deluca et al 11 proved that the insertion of Bi 3+ into the BaTiO 3 lattice promotes tetragonal distortion due to the effect of the stereochemically active lone-pair of Bi 3+ . This effect, however, seems to be compensated if a large cation (such as Yb) is introduced on the B-site.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations above that are based on simple arguments of ionic radii are, therefore, overly simplistic. In perovskite solid solutions such as (Na,Bi,Ba)TiO 3 and (Ba,Ca)TiO 3 , it has been shown that significant changes in ionicity between different cations and oxygen can result in anomalous lattice parameter changes and phase transition behaviors [35,36]. It is possible that a similar effect occurs in Si-doped HfO 2 .…”
Section: Combined Refinement Of Neutron and X-ray Diffraction Patternsmentioning
confidence: 94%